1991
DOI: 10.1037/0021-9010.76.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Unblocking brainstorms.

Abstract: Brainstorming groups have consistently produced fewer ideas than have the equivalent number of individuals working by themselves. These results have been attributed to social loafing, evaluation apprehension, and production blocking in groups. In this study, a new brainstorming technique--electronic brainstorming--that may reduce both production blocking and evaluation apprehension was assessed. Electronic and nonelectronic groups and nominal and interacting groups were compared in a 2 x 2 factorial design. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(237 citation statements)
references
References 7 publications
10
213
2
Order By: Relevance
“…While there is plenty of research that alludes to the benefits and potential of computers in education, there have been few systematic studies concerning the attitudes and beliefs of ESL students toward learning in a CAWC classroom and the personal, cultural, or course-based constraints that may impose on their learning and acquisition of language in such settings. In particular, gaps exist concerning whether existing findings (e.g., Easton et al, 1990;Gallupe et al, 1991;Steeb & Johnson, 1981;Valacich et al, 1996) about the improved decision quality and idea generation characteristic of computer-mediated writing groups are similar for ESL students.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…While there is plenty of research that alludes to the benefits and potential of computers in education, there have been few systematic studies concerning the attitudes and beliefs of ESL students toward learning in a CAWC classroom and the personal, cultural, or course-based constraints that may impose on their learning and acquisition of language in such settings. In particular, gaps exist concerning whether existing findings (e.g., Easton et al, 1990;Gallupe et al, 1991;Steeb & Johnson, 1981;Valacich et al, 1996) about the improved decision quality and idea generation characteristic of computer-mediated writing groups are similar for ESL students.…”
Section: Introductionmentioning
confidence: 97%
“…Recent research in the area of computer-mediated communication (CMC) and instruction has shown that compared with face-to-face groups, computer-mediated groups are more likely to make higher quality decisions about editing, revision, grammar, structure content, and feedback (Easton, George, Nunamaker, & Pendergast, 1990;Gallupe, Bastianutti, & Cooper, 1991;Steeb & Johnston, 1981), generate more ideas (Valacich, Paranka, George, & Nunamaker, 1996), and empower students with better communicative abilities. However, research on the effects of using technology in the teaching of writing courses is in its infancy: "Because research on computers and writing is a relatively new phenomenon and because the technology has changed dramatically over a short period of time, studies on any single aspect of computer assisted writing are scarce" (Ferris & Hedgcock, 1998, p. 267).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has frequently been found that groups of individuals create more ideas than brainstorming groups (Diehl and Stroebe, 1987). To avoid the underlying effects such as free riding and production blocking, electronic brainstorming systems have successfully been applied (Gallupe et al, 1991). Similarly, private workspaces could enhance productivity in other cases as well.…”
Section: Privacy Vs Awarenessmentioning
confidence: 99%
“…They conclude that computerized systems consisting of laptops and portable shared displays could be valuable tools to support group decision processes. Furthermore, studies have shown that computer support can have positive effects on brainstorming results (Gallupe et al, 1991). A recent example for an electronic brainstorming system is GroupMind (Shih et al, 2009), which supports collaborative brainstorming processes in both co-located and distributed settings (also using mind-maps).…”
Section: Brainstorming and Group Decision Support Systemsmentioning
confidence: 99%
“…Yet, research shows that process can be inhibited by group interaction, even in homogeneous teams. Members are often concerned about others' evaluation of their contributions (Diehl & Stroebe, 1987;Gallupe, Bastianutti, & Cooper, 1991). Further, groups tend to focus on information they have in common, rather than members' unique perspectives (Stasser, 1999).…”
Section: Team Learningmentioning
confidence: 99%